Opamp Inverting Amplifier: The case of non-inverting input not being connected to ground

What is the relation between $V_i$ and $V_o$ when the non-inverting input is supplied with a non-zero voltage level?

I have shared my formula derivation below, but I can't validate it since I can't find this special case anywhere on the internet.

Note: My interest comes from the circuit in this document (page 32, figure 25). simulate this circuit – Schematic created using CircuitLab

My work:

Let $A$ be the gain of the opamp at linear region, and $\pm V_{cc}$ is large enough not to saturate the opamp.

$$V_o = A(V_p - V_n)$$

From node voltages method:

$$V_n = \dfrac{\dfrac{V_i}{R_i} + \dfrac{V_o}{R_f}}{\dfrac{1}{R_i} + \dfrac{1}{R_f}} = \dfrac{R_iV_o + R_fV_i}{R_i + R_f}$$

Then we have:

$$V_o = A\left(V_p - V_n\right) = A\left(\dfrac{(R_i + R_f)V_p}{R_i + R_f} - \dfrac{R_iV_o + R_fV_i}{R_i + R_f} \right)$$

Rearranging the terms:

$$V_o + \dfrac{AR_iV_o}{R_i + R_f} = A\left(\dfrac{(R_i + R_f)V_p}{R_i + R_f} - \dfrac{R_fV_i}{R_i + R_f} \right) \\ \left[ \dfrac{AR_i}{R_i + R_f} + 1 \right] V_o = A\left(\dfrac{(R_i + R_f)V_p}{R_i + R_f} - \dfrac{R_fV_i}{R_i + R_f} \right) \\ \dfrac{(A+1)R_i + R_f}{R_i + R_f} V_o = \dfrac{A(R_i + R_f)V_p}{R_i + R_f} - \dfrac{AR_fV_i}{R_i + R_f} \\ \left[(A+1)R_i + R_f\right] V_o = \left[A(R_i + R_f)V_p\right] - \left[AR_fV_i\right] \\ V_o = \dfrac{A(R_i + R_f)V_p}{(A+1)R_i + R_f} - \dfrac{AR_fV_i}{(A+1)R_i + R_f} \\$$

If the gain $A$ is large enough, we can write:

$$\lim\limits_{A \to \infty} V_o = \lim\limits_{A \to \infty} \left[\dfrac{A(R_i + R_f)V_p}{(A+1)R_i + R_f} - \dfrac{AR_fV_i}{(A+1)R_i + R_f}\right] = \dfrac{R_i + R_f}{R_i} V_p - \dfrac{R_f}{R_i} V_i$$

Then the formula is:

$$\boxed{V_o = -\dfrac{R_f}{R_i} V_i + \dfrac{R_i + R_f}{R_i} V_p}$$

If $V_p=0$ we get the inverting amplifier equation:

$$V_o = -\dfrac{R_f}{R_i} V_i$$

And, if $V_i=0$ we get the non-inverting amplifier equation:

$$V_o = \dfrac{R_i + R_f}{R_i} V_p = \left(\dfrac{R_f}{R_i}+1\right) V_p$$

This looks like to be a mixed case in which it both works as inverting and non-inverting amplifier.

• Figure 28 on page 32 maybe? – Andy aka Feb 23 '15 at 22:27
• @Andyaka I meant the page of PDF, not the page numbers seen on the page footers. F28/P32 contains the same circuit though. – hkBattousai Feb 23 '15 at 22:41

So, if $I$ is the current flowing through $R_i$ and $R_f$, $$V_n=V_p$$ $$I=(V_n-V_i)/R_i=(V_o-V_n)/R_f$$ Rearranging: $$V_o=\frac{R_f}{R_i}(V_n-V_i)+V_n=\frac{R_f}{R_i}(V_p-V_i)+V_p = -\frac{R_f}{R_i}V_i+\frac{R_f+R_i}{R_i}V_p$$ Which is exactly your formula.